PERILAKU KONSUMSI AIR PADA MUSIM KEMARAU DI DUSUN PAMOR, KABUPATEN GROBOGAN - Ipung Purwanto (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2017)
Drought disaster in Grobogan District takes place almost every year. This research aims to study the household water consumption behavior during dry season. Precipitation data, soil map, and land cover map were collected. Historical information was also collected with snowball sampling and depth interview. Public perceptions were collected through Focus Group Discussion. Interview and direct observation were conducted to discover people behaviour in collecting water. Survey was also done to collect data on water consumption. Historical information, people perception and people behaviour were done by qualitative analysis. Regresion analysis was applied for water consumption with amount of household member and cattles ownership. The result were: 1) The drought occured due to water deficit from May to October, although annual water balance was surplus, 2) the history of drought has been going on for long time. 3) Searching and collecting water from river or other places were an obligation, 4) When their wells dry up, they search for water from water springs within 1-3 kilometers distance, 5) The amount of water consumption each day was 0.453 m3/people/day; 0.283 m3/cow/day, and 0.044 m/goat/day. This numbers can be applied as an input of the development plan of infrastructure to address drought and supply water needs in case of drought.